Risk and Protective Factors for Physical Activity Engagement Among Adolescents With Comorbid Asthma and Obesity. (15th July 2022) - Yourell, Jacqlyn; Koskela-Staples, Natalie; Doty, Jennifer; Fedele, David A
Abstract: Objective: The current study identifies levels of physical activity (PA) engagement among adolescents with neither asthma nor overweight/obesity (OW/OB), one, or both conditions. Risk and protective factors are examined across groups. Methods: Data from 8th, 9th, and 11th graders were obtained from the 2019 Minnesota Student Survey ( N  =   125, 164). One-way analysis of variance was used to assess PA levels across risk groups. Linear regressions were used to examine patterns of risk and protective factors for adolescent PA engagement across four groups (neither asthma nor OW/OB, asthma only, OW/OB only, and comorbid asthma + OW/OB). Results were stratified by race/ethnicity. Results: Adolescents with OW/OB only or asthma + OW/OB had significantly lower PA levels than youth with asthma only or neither condition ( M  =   3.65–3.67 days/week, SD  =   2.20 vs M  =   4.15–4.19 days/week, SD  =   2.16–2.17, p < .001). The following variables were associated with adolescent PA ( p < .001): Adult community care across all risk groups (β ranges = .13–.16), depressive symptoms among those with neither and both asthma + OW/OB (β's = –.10), and extracurriculars among those with asthma + OW/OB (β = .10). Extracurriculars and parent connectedness were protective for Hispanic adolescents. Conclusions: Adolescents with OW/OB had significantly lower levels of PA compared to those without, regardless of asthma status. Individual and relational factors influenced adolescent PA. Future research investigating factors influencing adolescent PA should consider depressive symptoms, connectedness to adults in the community, non-sport-related extracurricular activity involvement, and address disparities among minoritized youth.